2023
DOI: 10.3390/educsci13050494
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interprofessional Education on Health Profession Students’ Professional Identity

Gioia J. Ciani,
Gary Grimaldi,
Maribel Macalintal
et al.

Abstract: Establishing interprofessional identity is critical in preparing health care teams to work in collaborative environments and enhance efficacy of patient care. Accreditation standards for health profession programs have been implemented to include interprofessional education (IPE), yet there remains obfuscation regarding occupational therapy’s (OT) professional identity. The purpose of this prospective pre-post test study was to assess an experiential IPE event for health profession students (n = 170 from ten h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Students' development of their professional identity was another key area of perceived growth. These are consistent with research findings that both SL (Levy & Edmiston, 2015;Long & Gummelt, 2020;Nino et al, 2011) and IPE (Ciani et al, 2023;Haugland et al, 2019;Rishel et al, 2020) were related to social work students' professional identity development. An oft-repeated sentiment by students was their appreciation of being an essential part of the interprofessional team.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Students' development of their professional identity was another key area of perceived growth. These are consistent with research findings that both SL (Levy & Edmiston, 2015;Long & Gummelt, 2020;Nino et al, 2011) and IPE (Ciani et al, 2023;Haugland et al, 2019;Rishel et al, 2020) were related to social work students' professional identity development. An oft-repeated sentiment by students was their appreciation of being an essential part of the interprofessional team.…”
Section: Discussionsupporting
confidence: 92%
“…Social work students must understand their role, as well as the unique contributions they bring to the team (cf. Ciani et al, 2023). Rishel and colleagues (2020) examined social work professional identity of 61 MSW students who took part in an IPE training program designed to prepare students for practice in integrated health.…”
Section: Teams and Teamworkmentioning
confidence: 99%
“…The course sequence consists of (a) INTERACT 510: introduction to autism spectrum disorder (ASD) and interprofessional teaming, taught in the 16-week spring semester, (b) INTERACT 520: comprehensive treatment models for ASD, an intensive 2-week course offered in May, (c) INTERACT 530: interprofessional assessment of ASD, spanning approximately 4 weeks during June, (d) INTERACT 540: interprofessional intervention for ASD, which lasts approximately 4 weeks during July; and (e) INTERACT 550: capstone, a 16-week course in the fall semester. Courses incorporate didactic and active learning strategies associated with positive outcomes for learners, such as role play and team discussion of case studies (Ciani et al, 2023; Heath et al, 2015; Nowak et al, 2023). The curriculum is designed to increase scholars’ knowledge about autism and moderate to severe ID and to support their growth in the IPE Collaborative’s (IPEC) core competencies: (a) values and ethics, (b) roles and responsibilities, (c) interprofessional communication, and (d) teams and teamwork (IPEC, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Nowak et al (2023) demonstrated that clinical experiences embedded in IPE curriculum were associated with positive changes in medical students' attitudes about teamwork and roles/responsibilities. Ciani et al (2023) found that IPE that included the active learning strategies of role play and team-based case discussions increased occupational therapy students' understanding of the roles and responsibilities of their own discipline and other disciplines.…”
Section: Ipe Efficacymentioning
confidence: 99%
See 1 more Smart Citation